A National Survey of Neurological Monitoring Practice After Obstetric Regional Anaesthesia in the UK. Issue 1 (March 2018) - Roderick, E.; Hoyle, J.; Yentis, S.M.
Abstract : ( Anaesthesia . 2017;72:755–759) Neuraxial anaesthesia is widely used for both labor analgesia and cesarean delivery in the United Kingdom. The risk of neurological complications with these procedures is very low in the obstetric population. However, when they do occur, early detection and management are especially important as their consequences could be critical to the patient. The Third National Audit Project of the Royal College of Anaesthetists recommended that local guidelines be put in place that provide recommendations for patient monitoring to identify early signs and symptoms as well as a process for involving anesthesiologists when problems are identified. National guidelines have been developed that address postoperative monitoring of non-obstetric patients who have received neuraxial anesthesia. However, those guidelines intentionally exclude parturients, and national guidelines specific to the obstetric population still do not exist.